A mini mass spectrometer with a low noise Faraday detector. Issue 11 (16th April 2020) - Tang, Yang; Xu, Qian; Li, Dayu; Xu, Wei
Abstract : A low noise Faraday detector and a data processing method were developed for a miniature ion trap mass spectrometer. Abstract : An ion trap mass spectrometer is conventionally featured with an electron multiplier as its detector. However, an electron multiplier can typically work at pressures below 20 mTorr with a high voltage applied, which limits the further miniaturization of ion trap mass spectrometers. In this work, a low noise Faraday detector was developed and integrated in our miniature mass spectrometer instrument, and a post data processing method was applied to improve its performance. A limit of detection of 1 ng mL −1 was achieved, and quantitation performance and mass resolution were characterized. This technology could be useful in the further development of miniature mass spectrometers by increasing background pressures.